REVERSE ENGINEERING MODELING PROCESSING AND FABRICATION OF VORONOI PERFORATED ANKLE-FOOT ORTHOSIS - Emzain, Zakki Fuadi; Mufarrih, AM.; Hartono, Moh; Qosim, Nanang; Herlambang, Yusuf Dewantoro (Journal of Applied Engineering Science, 2024)
The ankle may not function optimally because of an ankle foot injury due to torn ligaments or foot drop, a post-stroke effect of hemiplegia. One treatment that can be done for sufferers of ankle foot injury and foot drop is using an ankle foot orthosis (AFO). Reverse engineering (RE) and additive manufacturing (AM) technologies can be utilized within the medical domain, specifically for producing prosthetic devices and orthoses that include optimal fit, lightweight characteristics, and cost-effectiveness. This study aims to create an optimized design for an ankle-foot orthosis by utilizing reverse engineering techniques, followed by an analysis of its performance using finite element simulation. The research process involved several key steps, namely 3D Scanning, CAD modeling, model analysis, and 3D printing. The findings of the model study after the implementation of Voronoi ventilation holes indicated that the highest equivalent stress observed in the model, with a shell element thickness of 1.4 mm, amounted to 21.12 MPa. This result represented an elevation of 11.74% compared to the model before introducing Voronoi ventilation holes. Nevertheless, there was a reduction in the model’s mass by 20.3%, specifically from an initial weight of 400.86 grams to a final weight of 319.51 grams. On the contrary, despite a fall in the safety factor, it continues to be considered safe, with a value of 2.84.